IMPLEMENTASI PERPRES 71 TAHUN 2012 TERHADAP PENGAMBIL ALIHAN TANAH HAK MILIK MASYARAKAT DALAM RANGKA PENGADAAN TANAH BAGI PEMBANGUNAN UNTUK KEPENTINGAN UMUM (Studi Pada Kantor Pertanahan Kabupaten Lampung Selatan) - Herlina Ratna; Reni Widyaningsih (Universitas Bandar Lampung (UBL), 2021)
he development of infrastructure such as toll roads certainly requires a very large area of land and a lot of ownership on it, so that land acquisition is carried outwhose procurement must be carried out by prioritizing the principles contained inArticle 33 paragraph (3) of the 1945 Constitution of the Republic of Indonesia. Writingproblems How is the implementation of the Presidential Regulation of the Republic ofIndonesia Number 71 of 2012 on the determination of property rights to land fordevelopment in the public interest in South Lampung Regency? the inhibiting factors forthe implementation of the Presidential Regulation of the Republic of Indonesia Number71 of 2012 in South Lampung Regency? The research method used is normative andempirical juridical, using secondary and primary data, obtained from literature studiesand field studies, and data analysis with qualitative juridical analysis. The results ofthis thesis research are the implementation of the Presidential Regulation of theRepublic of Indonesia Number 71 of 2012 which is carried out with applicable legalprovisions and the holders of land rights are given compensation for their land, but it isundeniable that the implementation is currently not maximally implemented due toobstacles and obstacles that arise. arise in the field process. The inhibiting factors are the incomplete evidence of ownership of land rights owned by the community, That there are still differences or errors in data obtained from the community (juridical data)with physical conditions in the field, There is a dispute over ownership of land rights,The basis for rights is made after the relevant governor's determination land acquisitionfor toll roads, Land ownership is still owned by other people. The suggestion is that theLand Office of South Lampung Regency should improve education to the publicregarding information about what conditions must be owned by the community in orderto get compensation related to the transfer of their land for the construction of toll roads.